A prospective study on the effects of Different methadone dosages on qtc Interval in opiate dependent individuals Receiving methadone maintenance therapy (mmt) - Hassan, Azlie (2012)
A PROSPECTIVE STUDY ON THE EFFECTS OF DIFFERENT METHADONE DOSAGES ON QTc INTERVAL AMONG OPIATE DEPENDENT INDIVIDUALS RECEIVING METHADONE MAINTENANCE THERAPY (MMT). Methadone is an effective treatment for opioid dependence and chronic pain. However, recent evidence suggests it also prolongs the QTc interval, resulting in torsade de pointes (TdP), a prerequisite to fatal cardiac arrhythmia, ventricular fibrillation (VF). Although higher doses of methadone are clearly more efficacious in reducing illicit opioid abuse, arrhythmia risk appears to increase in parallel creating an efficacy-safety paradox. This study investigates the effects of different methadone dosages on the QTc interval in opioid dependent individuals undergoing MMT over an eight week period. To compare the QTc interval duration between low and high dose methadone groups. To determine the correlation between QTc interval and different methadone doses. To determine the proportion of prolonged QTc interval amongst methadone treated patients at different methadone dosages. To determine the association of prolonged QTc interval between low and high dose methadone groups. A prospective cohort study for a six months duration was done from June until December 2010 on eligible subjects undergoing Methadone Maintenance Therapy (MMT) in HUSM. The QTc intervals were measured at the beginning of the study (week 0) and measured again during follow up at week 4 and week 8 of study period. Serum potassium, calcium and magnesium along with serum methadone levels were also measured at each visit. The association between prolonged QTc interval and different methadone dose groups as well as other parameters was analyzed using SPSS version 18.0. There were 46 patients enrolled into the study during the study period. No patient had a QTc interval of more than 500 ms during the study period. There were no statistically significant correlation between QTc interval and both clinical dose and plasma methadone level (r = 0.22,/? = 0.148 and r = 0.08,/? = 0.617 respectively). There was a marginally significant association between prolonged QTc interval and methadone dose group at week 0 [p = 0.044, OR 4.29 (0.98,18.72. In week 4, there was a significant association between prolonged QTc interval and methadone dose [p - 0.013, OR 5.18 (1.34,20.06)]. However, the QTc interval prolongation was not associated with different methadone dose in week 8 [p = 0.139, OR 2.44 (0.74,8.01)]. Further analysis with RM ANOVA revealed a significant increase of QTc interval over time (p = 0.005). We concluded that opiate dependent individuals who received MMT showed a progressive QTc interval prolongation over the course of methadone treatment. Subjects who were receiving methadone dose of greater than 80 mg per day are more likely to develop prolonged QTc interval compared to subjects receiving less than 80 mg of methadone daily. However, the effects of the different methadone dosages on QTc interval were not consistent throughout the study period, suggesting the complex and fluctuating nature of methadone induced QTc interval prolongation even when the dose remained constant.